(untitled) (Ágora Journal, 2022)
The world economic crisis and its external elements were analyzed during the COVID-19 pandemic, especially about refugees, which opened up to the world the line of action of the current system, from the perspective of the book ’The idea of Socialism’, by Axel Honneth. To this end, a survey of data relating to the world pandemic is carried out, with the aim of questioning how the capitalist ideal deals with situations where human rights and life are at the center of the problem. From this, adopting a dialectical method of research, a bibliographic review of Honneth’s Theory is undertaken regarding the socialist model,in order to seek the possibility of an alternative to the current economic system able to meet new social and economic expectations.